Liminality and Disinhibition in Online Language Learning - Cunningham, Una (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2011)
The aim of this paper is to bring theoretical concepts from other areas of scholarly research to bear on synchronous online education in a cross-disciplinary effort to shed light on what is going on by introducing systems of thought from other areas. The liminality and associated communitas which are found in synchronous online learning environments are examined for their possible consequences for learning in general and language learning in particular. Like computer-mediated communication, liminality has been associated with disinhibitory effects. Lack of excessive inhibition has been shown to have positive effects on second language production. The position of the online learner as “neither here nor there” or perhaps simultaneously both here and there is investigated and discussed.